A report of laser-assisted modified Widman flap for periodontal regeneration: Clinical and radiographic evaluation - Sanjeev Kumar Salaria; Veenu Madaan; Deepak Bala (Wolters Kluwer Medknow Publications, 2010)
Periodontitis is a relatively common disease. Various therapies have been recommended for its treatment which includes nonsurgical, antimicrobial, and surgical therapy. In recent years lasers have been used for all the three above-mentioned purposes. Lasers have been applied for hard and soft tissue debridement, contouring as well as the bacterial load reduction in the pocket. Here we present a case report of chronic periodontitis treated with the help of a new technique, laser-assisted modified Widman flap (LAMWF). The surgical procedure followed with a 980 nm diode laser has been described. The present case report resulted in significant pocket depth reduction, attachment gain, and radiographic evidence of bone fill. The laser-assisted modified Widman flap provided excellent results without complications and high patient as well as clinician satisfaction.